Analisis Sikap Belajar dan Kemampuan Kreativitas Siswa dalam Memecahkan Masalah Matematika - Risma Normalasari; Hamdan Sugilar; Sopyan Ali (UIN Sunan Gunung Djati Bandung, 2023)
The ability of creativity is needed to be able to support life, especially in solving problems in everyday life. In learning mathematics, creativity is one aspect that affects learning outcomes. This research was carried out with the aim of knowing students' learning attitudes and abilities in solving problems, especially in learning mathematics. The method used in this research is a survey method. The results showed that the level of student creativity was in the pretty good category. However, the ability of creativity still needs to be improved so that it can support students in learning activities